2005
DOI: 10.21273/hortsci.40.5.1493
|View full text |Cite
|
Sign up to set email alerts
|

Cabbage Yield and Glucosinolate Concentrations as Affected by Nitrogen and Sulfur Fertility

Abstract: Glucosinolates are a class of nitrogen (N) and sulfur (S) containing compounds shown to have cancer-preventing properties in animal models and widely found in cruciferous plants. The overall objective of this study was to determine whether N and S fertility affects glucosinolate concentrations in cabbage (Brassica oleracea L. Capitata group). Field studies on a sandy soil low in available N and S were conducted over a 2-year period with both green (`Grand Slam') and red (`Vor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
71
3
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 22 publications
16
71
3
2
Order By: Relevance
“…The availability of N and S and the N:S ratio has previously been shown to influence the content of GLS. 18,24,25,42 In the present study neither total N supply, estimated as potentially plant-available N, nor N:S ratio correlated with total GLS content; however, there was a positive correlation between total GLS content in broccoli and S content in fertilizer materials. The high total GLS level in broccoli fertilized with SS and MF, which had the highest S content among the fertilizer materials, and the low level of total GLS in broccoli fertilized with SM with low S content indicate that S supply might be more important for the total GLS content than N supply and N:S ratio at the current fertilizer rates.…”
Section: ■ Discussioncontrasting
confidence: 90%
“…The availability of N and S and the N:S ratio has previously been shown to influence the content of GLS. 18,24,25,42 In the present study neither total N supply, estimated as potentially plant-available N, nor N:S ratio correlated with total GLS content; however, there was a positive correlation between total GLS content in broccoli and S content in fertilizer materials. The high total GLS level in broccoli fertilized with SS and MF, which had the highest S content among the fertilizer materials, and the low level of total GLS in broccoli fertilized with SM with low S content indicate that S supply might be more important for the total GLS content than N supply and N:S ratio at the current fertilizer rates.…”
Section: ■ Discussioncontrasting
confidence: 90%
“…Kim et al (2002) found that glucosinolate content from the edible parts of B. rapa is strongly affected by nitrogen and sulphur applications. This was also stated by Rosen et al (2005) who showed that total glucosinolates and glucobrassicin content were maximized in cabbage cultivars grown at low nitrogen and high sulphur application rates.…”
Section: Environmental Factorssupporting
confidence: 65%
“…The influence of N and sulphur (S) on glucosinolate content in broccoli has been widely studied, but similar studies are lacking for cabbage and cauliflower (Table 1), with the exception of Rosen, Gardener, Hecht, Carmella, and Kenney (2005). Glucosinolate synthesis in broccoli requires optimal (i.e.…”
Section: Glucosinolatesmentioning
confidence: 99%
“…Once S supply is adequate, however, minimal N applications resulted in highest glucoraphanin content in broccoli (Table 1) (Jones et al, 2007), but N application rates that optimized glucoraphanin content in broccoli resulted in a significant decline in head weight (Jones et al, 2007) In a study with higher N application rates (50-600 kg ha À1 ), Omirou et al (2009) found glucoraphanin content in broccoli florets was maximized with a mid-range N application of 250 kg ha À1 . Growth stress caused by limited N also resulted in enhanced glucosinolate synthesis in pak choi (Shattuck & Wang, 1994), watercress (Kopsell et al, 2007a(Kopsell et al, , 2007b, and cabbage (Rosen et al, 2005) (Table 1). Jones et al (2007) postulated that poor N availability in broccoli florets may indirectly result in an increased availability of methionine for glucosinolate production, as suggested by Dick-Hennes and Buning-Pfaue (1992).…”
Section: Glucosinolatesmentioning
confidence: 99%